2022
DOI: 10.1257/aer.20201605
|View full text |Cite
|
Sign up to set email alerts
|

The End of Economic Growth? Unintended Consequences of a Declining Population

Abstract: In many models, economic growth is driven by people discovering new ideas. These models typically assume either a constant or growing population. However, in high income countries today, fertility is already below its replacement rate: women are having fewer than two children on average. It is a distinct possibility that global population will decline rather than stabilize in the long run. In standard models, this has profound implications: rather than continued exponential growth, living standards stagnate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Some of these responses cited that it was “basic economic theory.” Only 26% of participants mentioned the productive aspects of more people. Moreover, only 12 participants out of 200 (6%) provided reasoning that unambiguously supported the conclusion that more people lead to more resources, a mainstream conclusion in macroeconomic modeling (Jones, 2022); even in cases where participants did mention that having more people increases the production of goods or the number of available workers, they did not expect those efficiencies to translate into an overall increase in resources. Taken together, these data provide strong evidence that people are depletionist by default.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these responses cited that it was “basic economic theory.” Only 26% of participants mentioned the productive aspects of more people. Moreover, only 12 participants out of 200 (6%) provided reasoning that unambiguously supported the conclusion that more people lead to more resources, a mainstream conclusion in macroeconomic modeling (Jones, 2022); even in cases where participants did mention that having more people increases the production of goods or the number of available workers, they did not expect those efficiencies to translate into an overall increase in resources. Taken together, these data provide strong evidence that people are depletionist by default.…”
Section: Discussionmentioning
confidence: 99%
“…More people means more mouths to feed, but it also means more arms to work and more minds to innovate. Economic growth is driven by people discovering new ideas and the challenges of increased demand bring greater incentives for innovation, such that more people, perhaps counterintuitively, can lead to more abundance (Bricker & Ibbitson, 2019; Jones, 2022).…”
Section: Efficiency Neglectmentioning
confidence: 99%
“…For example, the emergence of stagflation risks, economic uncertainty, global financial markets, increasing inflationary pressures, declining global populations, and geopolitical situations. (Jones, 2022;Menueta et al, 2020;Bagchi et al, 2020;Lea, 2019). Wang & Wang (2022) have explained in their study that in certain cases, the dynamic cyclical model of economic growth will require efforts to overcome it such as the role of labor and entrepreneurship to achieve the creative potential for the common good.…”
Section: Economic Growth With Economic Cycles In the Halal Tourism Se...mentioning
confidence: 99%
“…Global economic growth after the economic recovery is projected to weaken. This is influenced by the increasing risk of stagflation, uncertainty, global financial markets, inflationary pressures, declining global population, and the geopolitical situation (Goestjahjanti et al, 2022;Jones, 2022;Bagchi et al, 2020;Lea, 2019). Studies reveal that the global environment is projected to weaken, while inflationary pressures will increase for 2022 and 2023.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been some debate, the vast majority of studies found that population aging has a negative effect on economic growth. According to a survey by Jones (2020), theoretical models of endogenous growth predict that a smaller population means fewer researchers who, in turn, generate fewer innovative ideas and ultimately lead to lower living standards. decreases firms' demand for older workers.…”
Section: Introductionmentioning
confidence: 99%